Upaya Meningkatkan Kompetensi Guru dalam Menyusun Silabus dan RPP Melalui Supervisi Akademik Berkelanjutan - Ade Kamaludin (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
This research is motivated by the low quality and quantity of teachers who make syllabi and lesson plans. The aims of this study include increasing teacher competence in preparing syllabus and Learning Implementation Plans through continuous academic supervision, finding out the appropriate steps in carrying out academic supervision, and measuring the increase in teacher competence in preparing syllabus and Learning Implementation Plans after continuous academic supervision. The results showed that the number of good-quality learning syllabuses increased from 27% to 83%. The number of good-quality learning implementation plans also increased from 30% to 90%.